Internal and external nasal dilatator in patients who snore: a comparison in clinical practice - Gelardi, Matteo; Porro, Giuseppe; Sterlicchio, Brigida; Quaranta, Nicola; Ciprandi, Giorgio; Group on Sonoring, Italian Study (Acta Biomedica Atenei Parmensis, 2019)
Snoring is a common symptom. The nasal valve area has the minimal cross-sectional area of the upper airways. So, nasal dilation may significantly reduce resistance to airflow and consequently could reduce snoring. Mechanical dilators may be used: they are external or internal. Nas-air® is a new internal nasal dilator. It was compared to a nasal strip (Rinazina Breathe Right®) in 41 outpatients who snore in an open study conducted in clinical practice. Snoring duration, assessed by smartphone, and visual analogue scale for the perception of sleep quality were measured before and during Nas-air® or nasal strip use. A significant reduction of snoring time and an improvement of sleep quality were achieved by wearing both devices. However, Nas-air® was effective in a larger number of patients and induced a better sleep quality than nasal strip. In conclusion, the present study demonstrates that Nas-air® is an internal nasal dilator able to reduce snoring time and to improve sleep quality, and may be preferred to the nasal strip by snoring patients.